Activities of the Muhammadiyah Student Association (IPM) at SMK Muhammadiyah Karanganyar - Agustina, Asri; Anshory, Muhammad Isa (Universitas Muhammadiyah Surakarta, 2023)
This study aims to analyze the implementation of character education through the organizational activities of the Muhammadiyah Student Association (IPM) at SMK Muhammadiyah Karanganyar. In addition, the paper attempts to determine the supporting and inhibiting factors for the implementation of character education through the organizational activities of the IPM at SMK Muhammadiyah Karanganyar. This study was conducted at SMK Muhammadiyah Karanganyar, Pekalongan Regency. The research method used in this research is a qualitative research method with a descriptive approach. The data collection techniques used were interviews, observation, and documentation with three stages of data analysis, namely data reduction, data presentation and data verification. The results of this study concluded that the implementation of character education through the organizational activities of the Muhammadiyah Student Association (IPM) at the Karanganyar Muhammadiyah Vocational School was carried out systematically, namely, through the planning, implementation and evaluation stages. Activities that support character education at the Karanganyar Muhammadiyah Vocational School are recitation of Qur’an, singing Indonesia Raya songs and Monday and Friday infaq program. Among the supporting factors of the program are collaboration with teachers, self-awareness of students, careful planning of activities while the inhibiting factors are lack of self-confidence, lack of communication, differences of opinion and lack of responsibility